Sources of finance for public-private partnership (PPP) in Poland - Roman Osinski (Central European Economic Journal (CEEJ), 2022)
This paper aims to present and discuss the already existing studies and try to uncover possible potential for further research on the topic of financial resources in public-private partnership (PPP) projects. The article presents the main relevant papers regarding financial resources and examines how deep the topic of financial sources has been explored in both academic and practical literature. Moreover, the article reviews Poland's PPP market and, particularly, types of used financial sources. The "Literature review" results show that there is a gap in studying the private sector and financial resources, especially in Polish PPPs. We attempt to close this gap by summarising the main factors that influence the choice of the source of financing PPPs. The Polish case shows that the main source of financing of PPP projects in Poland is bank loans and many projects have partial funding from various European Union (EU) programmes. Policymakers should pay attention to other financial resources in PPPs. Moreover, it would be fruitful to extend the Polish database of PPP projects with new factors that can simplify ex-post and ex-ante analysis.
Keywords: G10; G15; G29; 330; public-private partnership; financing source; capital market; finance; source of finance